All Days 2011
DOI: 10.2118/143983-ms
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Characterization and Modeling of the Capillary Transition Zone and Flow dynamics in the Oil Rim Reservoirs

Abstract: The oil rim reservoirs are referred to the reservoirs with limited oil column underlain with aquifer and overlain by a gas cap. In such reservoirs, the whole oil column can be in the capillary transition zone with a complex flow dynamics. In some cases, oil might have been displaced by imbibition process over geological time during the fluid migration history following the initial primary drainage. Understanding the capillary transition zone, displaced oil zone, saturation modeling, mobile oil distribution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Evidences from different fields presented in our previous work [1] showing the actual residual oil saturation could be far less than the reported Sor from the SCAL tests at the maximum oil saturation. Residual oil saturation significantly affects the mobile oil saturation and the amount of oil recovery.…”
Section: Well Water Cutmentioning
confidence: 51%
See 1 more Smart Citation
“…Evidences from different fields presented in our previous work [1] showing the actual residual oil saturation could be far less than the reported Sor from the SCAL tests at the maximum oil saturation. Residual oil saturation significantly affects the mobile oil saturation and the amount of oil recovery.…”
Section: Well Water Cutmentioning
confidence: 51%
“…The field background, capillary transition zone characterization and modeling concepts for the studied field were detailed in earlier publications [1,2]. Initial contractor for the field development concluded that the field was marginal due to low recovery factor (RF) based on the complexity of the flow dynamics, initial interpretation of appraisal wells and the technical limitations of the early 70s.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiation between capillary and apparent transition zones and reliable understanding of the volumetric assessment based on determination of their boundaries play a major role in project economy and the success of field development [1,2,3] . The failure of correct identification of CTZ leads to by-passing oil-rich footage of a producible zone or on the contrary, early breakthrough of water or miss-guided infill wells that could pave the way to economic failure of the project.…”
Section: Capillary Transition Zone (Ctz) 2 Apparent Transition Zone mentioning
confidence: 99%
“…The capillary transition zone is controlled by the balance of the capillary and buoyancy forces during the primary drainage process of oil migrating into an initially water filled reservoir trap. The height of the transition zone and its saturation distribution are determined by the range and distribution of pore sizes within the rock, as well as the interfacial force and density differences between the two immiscible fluids [1,2] .…”
Section: Atz Vs Ctzmentioning
confidence: 99%
“…It should be mentioned that the challenges on the Sw characterization in capillary transition zone is elaborated in detail elsewhere [12]. The original Sw log tends to predict more gas saturation with very negligible amount of irreducible water saturation and hence believed to be too optimistic.…”
Section: Field Examples Validation and Applicationmentioning
confidence: 99%